2012
DOI: 10.1017/s204017441200061x
|View full text |Cite
|
Sign up to set email alerts
|

Prematurity and programming: contribution of neonatal Intensive Care Unit interventions

Abstract: Contemporary clinical practice for the care of the prematurely born babies has markedly improved their rates of survival so that most of these babies are expected to grow up to live a healthy functional life. Since the clinical follow up is of short duration (years), only limited data are available to relate non-communicable diseases in adult life to events and interventions in the neonatal period. The major events that could have a programming effect include (1) Intrauterine growth restriction (2) Interruptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 121 publications
(252 reference statements)
0
5
0
1
Order By: Relevance
“…51 Numerous factors can influence nephrogenesis in premature infants, including growth restriction in utero, interruption of pregnancy with the associated alteration in redox state, adequacy of postnatal nutrition, and pharmacologic interventions after birth. 52 Premature infants that were SGA had fewer nephrons than did infants that were appropriate weight for gestational age (AGA), demonstrating the additional effect of growth restriction on prematurity. 53 Furthermore, premature infants with renal failure (defined as serum creatinine >152.52 μmol/l) have fewer nephrons as compared to those that do not develop renal failure.…”
Section: Renal Developmental Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…51 Numerous factors can influence nephrogenesis in premature infants, including growth restriction in utero, interruption of pregnancy with the associated alteration in redox state, adequacy of postnatal nutrition, and pharmacologic interventions after birth. 52 Premature infants that were SGA had fewer nephrons than did infants that were appropriate weight for gestational age (AGA), demonstrating the additional effect of growth restriction on prematurity. 53 Furthermore, premature infants with renal failure (defined as serum creatinine >152.52 μmol/l) have fewer nephrons as compared to those that do not develop renal failure.…”
Section: Renal Developmental Programmingmentioning
confidence: 99%
“…74 A reduced nephron number associated with premature delivery is a likely risk factor for acute kidney injury, although the severity of illness, exposure to nephrotoxic medications, and malnutrition are additionally likely to contribute. 52,75 No defined threshold of creatinine level currently exists to facilitate diagnosis of renal dysfunction in neonates. Consequently, increased awareness among clinicians is required to detect renal injury in affected individuals, to ensure minimization of subsequent renal damage, and to determine the requirement and course of long-term follow-up in premature infants.…”
Section: Effects On Hypertension and Kidney Diseasementioning
confidence: 99%
“…For example, in India it represents almost 25 to 30% of all births and is a major contributor to perinatal and neonatal morbidity and mortality and to subsequent impaired growth and stunting (Sachdev, 2001). The impact of intrauterine growth retardation and consequent low birth weight on the long term health of the offspring has now been established in large epidemiological studies in humans from different parts of the world and shown in animal models (Barker, 1994; Hales, 1997; Yajnik et al, 1995; Godfrey KM, 1998; Ozanne and Hales, 2002; Whincup et al, 2008; Warner and Ozanne, 2010; Kalhan and Wilson-Costello, 2013). The relationship between fetal growth and its regulation and nutritional, and endocrine interactions between the mother, the placenta and the fetus has been studied extensively (Murphy et al, 2006; Fowden and Forhead, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…При этом ряд технологий исключают из про-токолов, если доказаны их побочные или негатив-ные последствия. Так произошло с постнатальным использованием дексаметазона для предотвращения бронхолегочной дисплазии после сообщений о его негативном влиянии на развитие ЦНС [19].…”
Section: клинические протоколы в отделении интенсивной терапииunclassified